Study of reproductive performance and some biological characteristics of Eriphia verrucosa (Forskal, 1775) in Coast of Jableh, Syria - Adib Hasan Zeini; Moussa, Emtessal I (Mesopotamian Journal of Marine Sciences, 2023)
This study aimed to evaluate the reproductive performance of Eriphia verrucosa in Syrian waters for the first time. This study was conducted during the period between March 2021 and February 2022 in the coast of Jableh city, Syria. The total number of individuals collected was 110 individuals scattered between 50 females and 60 males, with a percentage of 45.4% - 54.5%, respectively. The results showed that spawning occurred during the period between March and July and a highest rate was during May. Fertility of Eriphia verrucosa ranged between 19512-116430 eggs\female, the width of the Carapace ranged between 3.5-6.4 cm, while the length of the Carapace ranged between 2.5-4.7 cm and the body weight ranged between 25.4-121.3 g.